Atypical Outcome of Klebsiella pneumoniae Endogenous Endophthalmitis - Saloua Ben Amor,; Safa Ben Aoun,; Mouna Rekik,; Amina Amouri,; Amira Trigui, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aim. Klebsiella pneumoniae (KP) can enter the bloodstream from initial infection sites and causes metastatic infections. Ocular infection is called endogenous endophthalmitis. It is considered as a sight-threatening emergency with a poor prognosis and permanent impairment. Our aim is to report a case of endogenous Klebsiella pneumoniae endophthalmitis (EKE) with an unexpected fortunate outcome. Observation. A 41-year-old patient with no significant past medical history presented with multiple liver abscesses and left endogenous endophthalmitis caused by KP. The diagnosis of hypervirulent KP was presumed. The patient was treated with systemic antibiotics and four intravitreal injections of antibiotics and corticosteroids. Immediate follow-up was marked by the occurring of a total retinal detachment. The patient had been lost to follow-up for six months in which he had taken oral and local antibiotics for two weeks and then presented to our department with total remission. Conclusion. This is a rare case reporting a good outcome of EKE presumably caused by hypervirulent KP and treated with four intravitreal injections of antibiotics, systemic and local antibiotics without vitrectomy.